Insight into the carboxyl transferase domain mechanism of pyruvate carboxylase from Rhizobium etli - Tonya N. Zeczycki (2018)
The effects of mutations in the active site of the carboxyl transferase domain of Rhizobium etli pyruvate carboxylase have been determined for the forward reaction to form oxaloacetate, the reverse reaction to form MgATP, the oxamate-induced decarboxylation of oxaloacetate, the phosphorylation of MgADP by carbamoyl phosphate, and the bicarbonate-dependent ATPase reaction. Additional studies with these mutants examined the effect of pyruvate and oxamate on the reactions of the biotin carboxylase domain. From these mutagenic studies, putative roles for catalytically relevant active site residues were assigned and a more accurate description of the mechanism of the carboxyl transferase domain is presented. The T882A mutant showed no catalytic activity for reactions involving the carboxyl transferase domain but surprisingly showed 7- and 3.5-fold increases in activity, as compared to that of the wild-type enzyme, for the ADP phosphorylation and bicarbonate-dependent ATPase reactions, respectively. Furthermore, the partial inhibition of the T882A-catalyzed BC domain reactions by oxamate and pyruvate further supports the critical role of Thr882 in the proton transfer between biotin and pyruvate in the carboxyl transferase domain. The catalytic mechanism appears to involve the decarboxylation of carboxybiotin and removal of a proton from Thr882 by the resulting biotin enolate with either a concerted or subsequent transfer of a proton from pyruvate to Thr882. The resulting enolpyruvate then reacts with CO2 to form oxaloacetate and complete the reaction. © 2009 American Chemical Society.